Comparative Literature Study On Resource Based View And Dynamic Capability Of The Firm - Purnomo, Bambang Raditya (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Corporate strategic management theory is always developing dynamically towards the formation of Resource-Based Theory, which emphasis on resource gaps has been widely used in many organizations in various industries. Over time, contemporary views of the firm have emerged to broaden the scope of the development of firm theory. Current company theory focuses more on the theory of the company's dynamic capabilities in carrying out product innovation accompanied by a high ability to act responsively, quickly and flexibly in using external competencies effectively. This paper attempts to provide a literature review regarding the importance of resource-based company theory and dynamic capability-based company theory as the main priority for organizational development.